THE INFLUENCE OF BRAND AWARENESS AND WORD OF MOUTH TOWARDS CUSTOMER PURCHASE DECISION ON NIANCARE MASK - Alfonsius; Tamara Ulansky (Universitas Putera Batam, 2023)
Medical equipment is one of the most important needs in the COVID-19 pandemic situation. One type of medical device that is indispensable today is a medical mask. Currently, medical masks have many brands, from unknown mask brands to well-known brands. As Niancare masks are still classified as new brand mask, the customers purchase decision are still unstable. In order for Niancare mask to compete with other well-known brands mask, the company must be able to increase the brand awareness and word of mouth so that customers can make purchasing decisions on Niancare brand mask. This study aims to determine whether there is an influence of brand awareness and word of mouth towards customer purchase decision of Niancare mask. This study uses a quantitative method by distributing questionnaires to 120 respondents who have ever bought and used Niancare mask. The data analysis method used is multiple linear regression by using SPSS version 25. The results showed that brand awareness and word of mouth simultaneously have significant influence towards customer purchase decision of Niancare mask. The results also showed that brand awareness partially has a significant influence towards customer purchase decision of Niancare mask as well as word of mouth partially has a significant influence towards customer purchase decision of Niancare mask. The most dominant factor of the two independent variables is word of mouth. This means, the higher the level of positive word of mouth and the greater the intensity of word of mouth, the higher the level of customer purchasing decision on Niancare brand mask